2018
DOI: 10.1007/s00216-018-1245-x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular mapping of living cells via synchrotron microFTIR and ZnS hemispheres

Abstract: FTIR imaging is a label-free, non-destructive method valuably exploited in the study of the biological process in living cells. However, the long wavelength/low spatial resolution and the strong absorbance of water are still key constrains in the application of IR microscopy ex vivo. In this work, a new retrofit approach based on the use of ZnS hemispheres is introduced to significantly improve the spatial resolution on live cell FTIR imaging. By means of two high refractive index domes sandwiching the sample,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Using synchrotron sources, the measurement of infrared spectra of living cells within a reasonable time frame has been successfully demonstrated, 27,28 including the characterisation of normal cells from carcinoma, 29 response of cells to mechanical stress, 30 apoptotic pathways, 31 chemical stress, 12 optical stimulation, 32 protein aggregation, 17,33 drug actions, 10 toxicity in living algae 34 and imaging with subcellular spatial resolution using ZnS hemispheres. 35 However, access to synchrotron facilities are limited and therefore measurements of living cells that can be carried out in an ordinary laboratory remains highly desirable. The use of bench-top (non-synchrotron) FTIR imaging to measure a population of living cells in transmission mode has shown that the SNR can be improved by using principle component reconstruction, allowing the distinguishing of cells before and after the treatment of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Using synchrotron sources, the measurement of infrared spectra of living cells within a reasonable time frame has been successfully demonstrated, 27,28 including the characterisation of normal cells from carcinoma, 29 response of cells to mechanical stress, 30 apoptotic pathways, 31 chemical stress, 12 optical stimulation, 32 protein aggregation, 17,33 drug actions, 10 toxicity in living algae 34 and imaging with subcellular spatial resolution using ZnS hemispheres. 35 However, access to synchrotron facilities are limited and therefore measurements of living cells that can be carried out in an ordinary laboratory remains highly desirable. The use of bench-top (non-synchrotron) FTIR imaging to measure a population of living cells in transmission mode has shown that the SNR can be improved by using principle component reconstruction, allowing the distinguishing of cells before and after the treatment of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared (FT-IR) spectroscopic imaging of live cells has been shown to be a promising tool for cell biology studies. 111 However, with the relatively long wavelength of infrared (IR) light especially in the so-called fingerprint region, the spatial resolution obtained is usually limited to approximately 3–30 µm with a standard FT-IR imaging microscope, depending on the numerical aperture (NA) of the objective and the wavelength of light used to generate the FT-IR image. 12,13 This limits the study to the analysis of single cells for most mammalian cells, which have sizes in the 10–50 µm range, with subcellular features of a few micrometers and below, resulting in unresolved subcellular information.…”
Section: Introductionmentioning
confidence: 99%
“…United Stated Air Force resolution target feature of 2.19 µm could be resolved at wavelength of 6 µm. 1 ZnS has the advantage of having a much lower spectral cut-off value of ∼700 cm −1 than CaF 2 , which has a cut-off value of ∼1000 cm −1 ; therefore, it does not increase the noise level below ∼1100 cm –1 region as in the case when CaF 2 is used. This is particularly beneficial for the linear array and single-point mapping systems where the detectors sensitivity range can reach down to 720 cm −1 and 650 cm −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…7 Synchrotron IR (SRIR) radiation, with three order of magnitude higher brilliance than thermal source, one order of magnitude larger spectral distribution than laser sources 8 and superior spectral stability to tunable lasers, is an ideal choice for FTIR microspectroscopy and imaging. In addition, the lowétendue of SRIR benefits FTIR such that the diffraction-limited resolution with high spectral quality can be achieved for both single detector 9 and FPA. To cope with the photon flux loss in confocal geometry, a high magnification objective (i.e.74x) is coupled to the FPA such that the oversampling can be implemented to realise the diffraction limited resolution with reasonable SNR level.…”
Section: Introductionmentioning
confidence: 99%